Figures 101-104. Pneumatic Apparatus - Palmer, Edward (Palmer's New Catalogue, with Three Hundred Engravings of Apparatus, Illustrative of Chemistry, Pneumatics, Frictional and Voltaic Electricity, Electro Magnetism, Optics, &c., 1840)
Figure 101. Single Transferer Figure 102. Double Transferer Figure 103. Guinea and Feather Apparatus with 2 falls Figure 104. Leslie's Pump for making Ice in any climate with three Receiver Plates each. These illustrations are part of Palmer's New Catalogue by Edward Palmer (1803-1872), regarded as the earliest, freely-accessible sales catalog of commercially available chemicals and scientific apparatus. The catalog provides insight into the costs and considerations of equipping laboratories during the early Victorian period. Featuring 292 engraved figures, the catalog is digitized in its entirety.
Keywords: Scientific apparatus and instruments; Commercial catalogs; Pneumatic machinery; Pneumatic tools; Pneumatics; Scientific apparatus and instruments industry